Modification of cell wall polysaccharides during retting of cassava roots. (15th December 2016) - Ngolong Ngea, Guillaume Legrand; Guillon, Fabienne; Essia Ngang, Jean Justin; Bonnin, Estelle; Bouchet, Brigitte; Saulnier, Luc
Highlights: Cell wall polysaccharides of cassava roots are cellulose, galactan rich pectins and xyloglucans. Retting deeply reduced galactose and galacturonic acid contents in cassava root cell walls. Enzyme profiling and immuno-labelling revealed that 1, 4 linkedd -galactans are degraded during retting. Endo -galactanase is likely a major enzymatic activity involved in the retting process. Abstract: Retting is an important step in traditional cassava processing that involves tissue softening of the roots to transform the cassava into flour and various food products. The tissue softening that occurs during retting was attributed to the degradation of cell wall pectins through the action of pectin-methylesterase and pectate-lyase that possibly originated from a microbial source or the cassava plant itself. Changes in cell wall composition were investigated during retting using chemical analysis, specific glycanase degradation and immuno-labelling of cell wall polysaccharides. Pectic 1, 4-β-d -galactan was the main cell wall polysaccharide affected during the retting of cassava roots. This result suggested that better control of pectic galactan degradation and a better understanding of the degradation mechanism by endogenous endo -galactanase and/or exogenous microbial enzymes might contribute to improve the texture properties of cassava products.